2020
DOI: 10.1002/wwp2.12039
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and the water–energy–food nexus in Africa: Evidence from Nigeria, Uganda, and Tanzania

Abstract: Water, energy, and food are necessary resources for well‐being and economic development. The physical and economic access to these resources in most Sub‐Saharan countries remains very low while the outbreak of COVID‐19 is projected to worsen the situation. Therefore, this study aims to assess the impacts of COVID‐19 on the access to water, energy, and food as well as to identify innovations in water sanitation and hygiene (WASH) practices and examine the current policy interventions in Nigeria, Uganda, and Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Open defecation is still widespread across SSA and the prevalence of handwashing with soap at critical times (after defecation and before eating) is still very low (Roche et al, 2017). However, a recent study covering Nigeria, Tanzania, and Uganda has reported an improvement in water, hygiene and sanitation during the COVID‐19 pandemic due to innovation and continuous mass sensitization (Durodola et al, 2020). It is widely reported that access to WSS services in schools has a positive impact on school attendance rates among adolescent girls and can enhance health and hygienic behavior among children in SSA.…”
Section: Water Security Challenges Facing Sub‐saharan Africamentioning
confidence: 99%
“…Open defecation is still widespread across SSA and the prevalence of handwashing with soap at critical times (after defecation and before eating) is still very low (Roche et al, 2017). However, a recent study covering Nigeria, Tanzania, and Uganda has reported an improvement in water, hygiene and sanitation during the COVID‐19 pandemic due to innovation and continuous mass sensitization (Durodola et al, 2020). It is widely reported that access to WSS services in schools has a positive impact on school attendance rates among adolescent girls and can enhance health and hygienic behavior among children in SSA.…”
Section: Water Security Challenges Facing Sub‐saharan Africamentioning
confidence: 99%
“…Since 2020, the world has been facing the devastating effects of the COVID-19 pandemic, which has had a direct impact on FEW security [ 26 , 27 , 28 ] in terms of both demand-side and supply-side disruptions (overview presented in Figure 2 ). For instance, nearly 2.1 billion people worldwide already lacked access to safely managed drinking water [ 59 ], and so frequent handwashing has emerged as a constrained resource when trying to follow the World Health Organization’s advisory on hygiene.…”
Section: Growing Relevance Of Urban–rural Linkage For Few Securitymentioning
confidence: 99%
“…A great deal of existing literature focuses on FEW sectors independently [ 21 , 22 , 23 ], however few studies have discussed the relationship between urban–rural partnership and the FEW nexus [ 24 , 25 ]. Some studies related to the FEW nexus and COVID-19 have also been published [ 26 , 27 , 28 ]. However, the importance of urban–rural partnerships to strengthen the FEW nexus for the post COVID-19 era has not yet been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The GHA established water, energy, food, biodiversity, and human health policies. Moreover, some studies explored WEF nexus via single study areas, for example, Rwanda and Ethiopia [45], Uganda and Tanzania [46], and Kenya [47], but cross-sectoral interlinkages between WEFBH nexus, their impacts, and consequences are largely unknown and underresearched. The GHA is a promising area that can facilitate us to understand the WEFBH nexus because of the aforementioned issues.…”
Section: Introductionmentioning
confidence: 99%